Control of Ectoparasitic Monogenean Infestation on GIFT Tilapia (Oreochromis sp.) using Salt Addition - Yani Hadiroseyani; L.S. Harti; Sri Nuryati (Jurnal Akuakultur Indonesia)
Ectoparasitic monogenean infestation is one of fish diseases which may cause mass mortality, therefore controlling the parasites is one of the important factors to ensure the success of aquaculture activities. Salt addition is one of disease curative and controlling techniques which is cheap, easy and environmental friendly as well as effective to control ectoparasites in freshwater environment. The objectives of this study were to examine monogenean parasites species in GIFT (Genetically Improved Farmed Tilapia) tilapia, their tolerance to salt concentration and the most effective salt concentration to control the parasites. Identification, intensity and prevalence of parasitic monogenean were carried out on the external parts (body surface, fins and gills) of 31 fishes. Subsequently, two different experiments were carried out  to determine parasites and fish resistance on various salt concentration at a range of 0 - 24 g/l with an interval of 2 g/l. To confirm the results of previous experiment, parasites infected fish was immersed in salt water at various concentration based on previous experiments. Two genera of monogenean were identified in GIFT tilapia, i.e. Gyrodactylus sp. on body surface and fins, and Cichlidogyrus sp. on gills with the same prevalence (100%). The intensity of those parasites was different, namely 27.84 ind/fish for Gyrodactylus sp. and 6.06 ind/fish for Cichlidogyrus sp. The intensity of both parasites was found to be lower as salt concentration increase. Salt concentration of 24 g/l was the most effective concentration to reduce parasites infestation and could totally treat the infested fish within 6 days.